2009
DOI: 10.1203/pdr.0b013e3181b454a4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Mediated Down-Regulation of Hepatobiliary Transporters Contributes to Intrahepatic Cholestasis and Liver Damage in Murine Biliary Atresia

Abstract: ABSTRACT:To investigate the hypothesis that during the development of biliary atresia, early changes in hepatobiliary transport are mainly related to the inflammatory process and lead to intrahepatic cholestasis and subsequent liver injury, livers from mice with rhesus rotavirus-induced biliary atresia were analyzed for mRNA expression of hepatobiliary transporters, nuclear receptors, and inflammatory cytokines. Seven days after inoculation, despite high bile acid concentrations in the liver, gene expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Observed increases in basolateral expression of Abcc3 and Abcc1 likely served to shuttle excess bile acids from hepatocytes into maternal blood. The changes in expression of these transporters and increased serum bile acids are consistent with other animal models of inflammation-induced cholestasis (Vos et al, 1998;McGillicuddy et al, 2009;Yang et al, 2009;Kosters and Karpen, 2010). It is believed that increased expression of basolateral efflux transporters is a homeostatic mechanism evoked to protect hepatocytes (Wagner et al, 2009;Keppler, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Observed increases in basolateral expression of Abcc3 and Abcc1 likely served to shuttle excess bile acids from hepatocytes into maternal blood. The changes in expression of these transporters and increased serum bile acids are consistent with other animal models of inflammation-induced cholestasis (Vos et al, 1998;McGillicuddy et al, 2009;Yang et al, 2009;Kosters and Karpen, 2010). It is believed that increased expression of basolateral efflux transporters is a homeostatic mechanism evoked to protect hepatocytes (Wagner et al, 2009;Keppler, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…SP functions as a neurotransmitter and inflammatory mediator and is also involved in the regulation of bile secretion, biliary dynamics and liver innervations. A role for hepatobiliary transporters (particularly Fxr) in murine BA has recently been reported (33).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of total bile acids have been reported in pregnant rats with obstructive cholestasis (Hassan and Subbiah, 1980;Serrano et al, 2003). Likewise, studies in cholestatic nonpregnant rodents also reported an increase in total bile acids Yang et al, 2009). Repeated poly(I:C) administration over 28 weeks has been reported to induce the development of primary biliary cirrhosis in mice (Okada et al, 2005); however, it is unknown whether single doses of poly(I:C) can induce cholestasis.…”
Section: Viral Infection Model Affects Transporters In Pregnancymentioning
confidence: 99%
“…Furthermore, bilirubin accumulation may be a slower process than changes in accumulation of bile acids. Indeed, a recent study has shown that bile salt levels in the liver were profoundly higher in infected mice much sooner than the onset of direct hyperbilirubinemia (Yang et al, 2009). Studies of duration longer than 24 h may be helpful in clarifying the regulation of bilirubin during maternal infections.…”
Section: Viral Infection Model Affects Transporters In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation